OV21/PETROC: A Randomized Gynecologic Cancer Intergroup Phase II Study of Intraperitoneal Versus Intravenous Chemotherapy Following Neoadjuvant Chemotherapy and Optimal Debulking Surgery in Epithelial Ovarian Cancer. Issue 4 (April 2018) - Provencher, D. M.; Gallagher, C. J.; Parulekar, W. R.; Ledermann, J. A.; Armstrong, D. K.; Brundage, M.; Gourley, C.; Romero, I.; Gonzalez-Martin, A.; Feeney, M.; Bessette, P.; Hall, M.; et al.
Abstract : (Abstracted from Ann Oncol 2018;29(2):431–438) The use of neoadjuvant chemotherapy (NACT) prior to surgical debulking is increasingly used for advanced epithelial ovarian cancer (EOC). In women with EOC, the principal site of disease is the peritoneal cavity. As a means of increasing the dose intensity delivered to the tumor, intraperitoneal (IP) chemotherapy has been investigated. Three randomized clinical trials and a meta-analysis have demonstrated improved survival for women with stage III EOC who—following optimal, primary debulking surgery—received a combination of intravenous (IV) and IP chemotherapy. Updated data from Gynecologic Oncology Group trial 172 (GOG 172), the most recent of these trials, reported continued benefit for women who had received the experimental arm. However, the use of IP/IV chemotherapy for advanced-stage EOC remains controversial. There has been a continuing debate on the impact of drug scheduling on the benefits of IP and concern over the toxicity of IP cisplatin used in the positive studies, compared with IV carboplatin.